QUANTIFYING PHYSICAL ACTIVITY LEVELS IN OLDER, OBESE PATIENTS WITH HEART FAILURE - Manning, Melissa Elizabeth (Wake Forest University, 2021)
Interventions utilizing caloric restriction and exercise training have been shown to improve exercise capacity and weight loss in patients with heart failure with a preserved ejection fraction (HFpEF). These interventions are particularly important in this population as the majority are overweight or obese and proven pharmacotherapy is lacking. While accelerometers allow for objective measurement of physical activity (PA), few studies have examined their use in older, obese patients with HFpEF. Furthermore, cut-points establishing light-intensity and moderate-to-vigorous intensity (MVPA) have not been validated in older, clinical populations, including patients with HFpEF. For this study, wrist-worn, tri-axial accelerometers were used to record free-living PA data in subjects (n=9) during one week of the SECRET II exercise training intervention. Cut-points based on accelerometry and indirect calorimetry were calculated using linear regression. Steps/day (9,424+860) as well as minutes/day of light (365+39) and MVPA (36+6) were measured and found to be higher than reported in prior studies of patients with HF. In fact, the older, obese patients with HFpEF in this study appeared to meet national guideline PA recommendations for healthy adults (7,000-8,000 steps/day, 150 minutes/week MVPA). In contrast to previous reports, no significant differences were found when comparing PA levels on days the subjects performed a center-based, structured exercise session (SES) versus “non-SES” days, including weekdays and weekends. Lack of significant differences may have been due to the small sample size, as effect sizes suggest there may be differences in PA levels across the week. Physical activity energy expenditure (PAEE) predicted by the wrist-worn device was found to significantly underestimate PAEE measured using indirect calorimetry (-0.020[-0.025- -0.014] kcals/kg/min), but this finding may be due to the lack of wrist-based algorithms for predicting PAEE. To our knowledge, this was the first study to quantify PA levels of older, obese patients with HFpEF undergoing an exercise training intervention and to identify wrist-based cut-points for determining PAEE in this population. A larger study is needed to confirm these findings.